1967
DOI: 10.1007/bf01439081
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenese der Sigma-Diverticulitis und die Indikation zur Resektionsbehandlung

Abstract: Abt. Chirurgie der Med. Fakulti~t der X~hein.-Westf. Techn. ttochschule Aachen (Vorstand: o. Prof. Dr. M. l~mrrn~sc~nlD) Eingegangen am 16. Februar ~967 Das erworbene Pulsionsdivertikel des Dickdarms besitzt eine eigene pathologisch-anatomische, patho-physiologische und klinische Erkennungsgeschiehte. Sie spiegelt sieh im Wandel der Behandlungsindikation wider. KS~TE war im Jakre 192i bereits seiner Entwicldung voraus, als er die Diverticulitis mit der Appendicitis auf eine Stufe stellte. Nach ibm postulierten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Comparative histological studies have confirmed the abnormalities in the muscles and nerve plexus (Becker,1976).The anatomical alterations are accompanied functionally by the formation of"segmental high pressure chambers"as described by Reifferscheid(1967).These are formed by extreme haustration and lead to high segmental pressure which Parks and Connel(1969)were able to demonstrate by open-end catheterization. Slack(1962)and Reiffersheid(1967)drew particular attention to changes in the vascular course which occur with advancing age and are simultaneously accompanied by a reduction of connective tissue.…”
Section: Pathogenesismentioning
confidence: 88%
“…Comparative histological studies have confirmed the abnormalities in the muscles and nerve plexus (Becker,1976).The anatomical alterations are accompanied functionally by the formation of"segmental high pressure chambers"as described by Reifferscheid(1967).These are formed by extreme haustration and lead to high segmental pressure which Parks and Connel(1969)were able to demonstrate by open-end catheterization. Slack(1962)and Reiffersheid(1967)drew particular attention to changes in the vascular course which occur with advancing age and are simultaneously accompanied by a reduction of connective tissue.…”
Section: Pathogenesismentioning
confidence: 88%